2004
DOI: 10.1007/s11661-006-0221-9
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the age-hardening behavior of Al-Si-Cu alloys

Abstract: We describe a new approach for modeling the age-hardening behavior of Al-Si-Cu cast alloys, that utilizes recently proposed micromechanical models of precipitation strengthening which connect key microstructural parameters for realistic precipitate morphologies (e.g., {100} plates) with the agehardening response. This approach is illustrated and tested for a series of 319-type Al alloys (which we refer to as W319), where the microstructural parameters of Ј plates measured by transmission electron microscopy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(31 citation statements)
references
References 25 publications
3
28
0
Order By: Relevance
“…[249] Whereas it is now possible to generate a microstructure containing both prismatic and basal plates in some magnesium alloys such as those based on the Mg-Gd-YZn system, and the basal plates in such a microstructure have a large aspect ratio, the aspect ratio and number density of the prismatic plates are much lower than those typical of precipitate plates formed in highstrength aluminum alloys. In high-strength precipitation-hardened aluminum alloys, the maximum hardness and yield strength is commonly associated with microstructures containing a high density of {100} a and {111} a precipitate plates of large aspect ratio (typically above 40:1) [245,250] (Figure 35), and these strengthening precipitates are often intermediate or equilibrium phases that are intrinsically stronger than G.P. zones and metastable precipitates formed in the early stage of aging.…”
Section: Microstructural Design For Higher Strengthmentioning
confidence: 99%
“…[249] Whereas it is now possible to generate a microstructure containing both prismatic and basal plates in some magnesium alloys such as those based on the Mg-Gd-YZn system, and the basal plates in such a microstructure have a large aspect ratio, the aspect ratio and number density of the prismatic plates are much lower than those typical of precipitate plates formed in highstrength aluminum alloys. In high-strength precipitation-hardened aluminum alloys, the maximum hardness and yield strength is commonly associated with microstructures containing a high density of {100} a and {111} a precipitate plates of large aspect ratio (typically above 40:1) [245,250] (Figure 35), and these strengthening precipitates are often intermediate or equilibrium phases that are intrinsically stronger than G.P. zones and metastable precipitates formed in the early stage of aging.…”
Section: Microstructural Design For Higher Strengthmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] However, these models only describe either the thermodynamics and kinetics for the precipitation process or the characteristics, sizes, and shapes of the precipitates on strengthening. Nothing had been taken into account to connect these two aspects until Shercliff and Ashby [11,12] made a first attempt to make a relationship between the process parameters (such as composition, aging temperature, and time) and the yield strength or hardness.…”
Section: Introductionmentioning
confidence: 99%
“…θ-Al 2 Cu has a structure (space group is I4/mcm) with lattice parameters a = 0.607 nm and c = 0.487 nm, and θ′ phase with tetragonal structure and a = 0.404 nm, c = 0.58 nm, the space group is I4m2 [26,27]. It has been confirmed that the ordered metastable θ′-phase imparts the largest strengthening effect in primary α-Al phase [28]. The θ′ precipitates have a platelet morphology with coherent (0 0 1) θ′ || {0 0 1} α-Al interfaces parallel to their broad faces.…”
Section: Effect Of Solution and Ageing Heat Treatment On The Microstrmentioning
confidence: 89%